2020
DOI: 10.2478/johh-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of vegetation on dam break flood waves

Abstract: Dams have an important role in the industrial development of countries. Irrespective of the reason for dam break, the flood can cause devastating disasters with loss of life and property especially in densely populated areas. In this study, the effects of the vegetation on the flood wave propagation in case of dam break were investigated experimentally by using the distorted physical model of Ürkmez Dam. The horizontal and vertical scales of the distorted physical model are 1/150 and 1/30, respectively. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The flow depth and velocity measurements presented and analyzed in the following sections are the averages of these three experiments. The so obtained results in the case of the existence of partial vegetation were compared to those obtained in the case of the absence of vegetation and also with the available experimental results obtained by Oguzhan and Aksoy [10] in the case of water depth of 98 cm. As shown in Figure 14, Oguzhan and Aksoy [10] realized their experiments on the distorted physical model of dense vegetation.…”
Section: Experimental Findingsmentioning
confidence: 78%
See 2 more Smart Citations
“…The flow depth and velocity measurements presented and analyzed in the following sections are the averages of these three experiments. The so obtained results in the case of the existence of partial vegetation were compared to those obtained in the case of the absence of vegetation and also with the available experimental results obtained by Oguzhan and Aksoy [10] in the case of water depth of 98 cm. As shown in Figure 14, Oguzhan and Aksoy [10] realized their experiments on the distorted physical model of dense vegetation.…”
Section: Experimental Findingsmentioning
confidence: 78%
“…Guney et al [9], investigated experimentally the flood propagation due to partial dam break resulting from a trapezoid-shaped breach by using the distorted physical model of Urkmez Dam. The experimental results show that the Urkmez area can be flooded in a matter of minutes, at depths reaching up to 3 m. The flood wave front could reach the residential areas in 2 min and the sea coast in 4 m. Oguzhan and Aksoy [10], differently from this study presented here, investigated experimentally the effects of more dense vegetation on the flood wave propagation in the case of dam break by using the distorted physical model of Urkmez Dam. The dam break scenarios were achieved by means of rectangular and triangular gates for the dam reservoir levels 98 cm, 88 cm and 80 cm.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In densely populated areas, a flood due to a dam rupture can cause a devastating disaster with loss of life and property. The time required to warn people living below the reservoir is very short in the event of a flood caused by a dam rupture (Oguzhan, and Aksoy, 2020;Xu et al, 2012). May 2021 was extremely cold and very wet in Slovakia.…”
Section: Introductionmentioning
confidence: 99%
“…The Physical models should be used as supplement and calibration of Numerical models [12]. Some studies found that the vegetation and dam break shape play an important role in dam break flood wave [13]. Rock-fill dam break flood analysis is a very important basic work in early warning and emergency rescue work, and the accuracy of dam breach flood prediction can directly affect the formulation and implementation of emergency treatment plans; among them, the prediction of dam break durations is a prerequisite for risk assessment and emergency response [14].…”
Section: Introductionmentioning
confidence: 99%